2018
DOI: 10.1371/journal.pone.0194062
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D concentrations in hospitalized critically ill dogs

Abstract: Hypovitaminosis D has been extensively documented in critically ill humans. However, whether or not critically ill dogs have alterations in vitamin D concentrations remains unconfirmed. The primary aims of our study were to compare serum 25-hydroxycholecalciferol [25(OH)D] concentrations in critically ill dogs with healthy control dogs, determine the prognostic utility of serum 25(OH)D concentration as a biomarker in critically ill dogs, and to assess if serum 25(OH)D concentrations in critically ill dogs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 51 publications
(52 reference statements)
1
36
1
Order By: Relevance
“…Kim et al (2017) observed that dogs that survived to acute pancreatitis had concentrations of 25(OH)D higher than concentrations observed in dogs that died due to this disease before the beginning of treatment. Jaffey, Backus, McDaniel, and DeClue (2018) found that dogs critically ill or with sepsis had lower serum 25(OH)D concentrations compared to healthy control dogs. Besides, serum 25(OH)D was considered a good predictor of survival for dogs in the intensive care unit and 30 days after discharge and it presented a correlation with illness severity.…”
Section: Vitamin D As a Predictor Of Mortalitymentioning
confidence: 89%
See 1 more Smart Citation
“…Kim et al (2017) observed that dogs that survived to acute pancreatitis had concentrations of 25(OH)D higher than concentrations observed in dogs that died due to this disease before the beginning of treatment. Jaffey, Backus, McDaniel, and DeClue (2018) found that dogs critically ill or with sepsis had lower serum 25(OH)D concentrations compared to healthy control dogs. Besides, serum 25(OH)D was considered a good predictor of survival for dogs in the intensive care unit and 30 days after discharge and it presented a correlation with illness severity.…”
Section: Vitamin D As a Predictor Of Mortalitymentioning
confidence: 89%
“…(Melamed et al, 2008). Jaffey, Backus, McDaniel, and DeClue (2018) found that dogs critically ill or with sepsis had lower serum 25(OH)D concentrations compared to healthy control dogs. was not considered a predictor of mortality as there was not a linear regression .…”
Section: In Humans Vitamin D Supplementation In Chf Patients Has Beenmentioning
confidence: 99%
“…Another limitation is that we enrolled only apparently healthy dogs. Calcitriol could have a different effect on shelter dogs that were systemically ill because they would be expected to have decreased serum 25(OH) D concentrations compared to healthy dogs [20]. Humans that are vitamin D deficient experience the most clinical benefit when supplemented with oral vitamin D [22].…”
Section: Discussionmentioning
confidence: 99%
“…Hypovitaminosis D has been identi ed in many infectious diseases in dogs including leishmaniasis, babesiosis, spirocercosis, blastomycosis, and bacterial sepsis, which suggests that like people, vitamin D could have an important protective role in the canine innate immune response (16)(17)(18)(19)(20). This theory is corroborated by early in vitro studies in healthy and critically ill dogs that demonstrated incubation of blood with calcitriol, decreased leukocyte production of the pro-in ammatory cytokine tumor-necrosis factor (TNF)-α in a concentration dependent manner (11,21).…”
Section: Introductionmentioning
confidence: 99%